Ստեփանոս Մալխասեանցը, «Պատմագիրք հայոց» մատենաշարը և Նորայր Բիւզանդացին - Տէր-Վարդանեան, Գէորգ
The author characterizes and assesses the work of Stepanos Malkhaseants, Norayr Biuzandatsi, and partly of Martiros Minasyan, demonstrating its importance in the development of Armenian philology. Furthermore, the necessity of a mul-tivolume publication of their works is stressed. The article is supplemented by a new edition of two articles by S. Malkhaseants: “From Old Ages” and “Forgotten or Not?”, as well as by Malkhaseants’s four letters to Norayr Byuzandatsi. These are the most important documents related to the editorial principles of the series Armenian Historiographers. They are significant for scholars interested in textological questions. В статье в общих чертах охарактеризованы и оценены заслуги Степаносa Малхасянца, Норайра Бюзандаци и, частично, Мартироса Минасяна перед филологической наукой, обоснована важность издания многотомников научных трудов этих ученых, переизданы две статьи С. Малхасянца – “Из древних веков” и “Забыт или не забыт?”, а также четыре письма С. Малха-сянца к Норайру Бюзандаци. Эта совокупность важнейших документов освещает формирование принципов издания серии “Историографы Армении.” Знакомство с ними очень важно для филологов, интересующихся армянской текстологией.
Keywords: Գրաբար բնագրերի քննութիւն